PENGARUH EDUKASI MEDIA BOOKLET TERHADAP PENGETAHUAN DAN SIKAP ORANG TUA TENTANG IMUNISASI DASAR PADA MASA PANDEMI COVID-19 - Eny Hastuti Hastuti; Sari Wahyunita; Aesty Rahayu; Wahyudi Wahyudi (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2021)
The Indonesian government is taking several steps to ensure the control of COVID-19 and strengthen the capacity of the health care system to handle the pandemic period. One of them is the coverage of basic immunization to prevent diseases in children such as measles, rubella, and diphtheria which is decreasing, including the number of immunization coverage for diphtheria, pertussis, tetanus (DPT3) and measles and rubella (MR1) has decreased by more than 35%. Immunization services are reopened to prevent Extraordinary Events (KLB) of diseases in children that can be prevented by immunization (PD3I), to socialize a series of guidelines, standard operating procedures (SOP), as well as communication, information, and education (KIE). This study aims to determine the effect of booklet media education on parents' knowledge and attitudes towards basic immunization during the COVID-19 pandemic. Research Design Nonrandomized pre-test post-test with control group design. The total sample of 158 respondents was divided into 2 groups, the intervention group which was educated with booklet media and the control group without booklet education. The results showed that booklet media education was very influential (p = 0.001) on parents' knowledge and attitudes about basic immunization during the COVID-19 pandemic, this proves that booklet media is a communication tool that can be used by health workers to help increase parents' knowledge so as not to worry about bringing children to health services to keep immunizing during this COVID-19 pandemic.